Knowledge produced about mental health and solidarity economy: a scope review - Manente Mazaro, Lisabelle; de Góes Camargo, Mariane; Aparecida de Oliveira Lussi, Isabela (Cooperativismo & Desarrollo, 2022)
The (re)insertion of people under psychological distress in the work occurred expressively through solidarity economy. Considering the absence of previous review studies addressing this theme, the proposal for the present study emerged. The purpose is characterize and analyze the relevant literature on solidarity economy and mental health. This is a scoping review conducted at online databases using descriptive data analysis. Forty-two studies, all published in Portuguese, were identified between 2007 and 2020: 25 articles, 14 master’s theses, and three doctoral dissertations. The studies were predominantly conducted using the qualitative approach, and solidarity economy, deinstitutionalization, and psychosocial rehabilitation were the main theoretical frameworks adopted by the authors. The importance of this scoping review is emphasized, since it identified and analyzed the scientific production in this field, as well as pointed out gaps that can guide a research agenda.